Habitual instigation and habitual execution: definition, measurement, and effects on behaviour frequency - Gardner,B; Phillips,A; Judah,GD (British Journal of Health Psychology, 2016)
Objectives‘Habit’ is a process whereby situational cues generate behaviour automatically, via activation of learned cue–behaviour associations. This article presents a conceptual and empirical rationale for distinguishing between two manifestations of habit in health behaviour, triggering selection and initiation of an action (‘habitual instigation’), or automating progression through subactions required to complete action (‘habitual execution’). We propose that habitual instigation accounts for habit–action relationships, and is the manifestation captured by the Self-Report Habit Index (SRHI), the dominant measure in health psychology.DesignConceptual analysis and prospective survey.MethodsStudent participants (N = 229) completed measures of intentions, the original, non-specific SRHI, an instigation-specific SRHI variant, an execution-specific variant, and, 1 week later, behaviour, in three health domains (flossing, snacking, and breakfast consumption). Effects of habitual instigation and execution on behaviour were modelled using regression analyses, with simple slope analysis to test habit–intention interactions. Relationships between instigation, execution, and non-specific SRHI variants were assessed via correlations and factor analyses.ResultsThe instigation-SRHI was uniformly more predictive of behaviour frequency than the execution-SRHI and corresponded more closely with the original SRHI in correlation and factor analyses.ConclusionsFurther, experimental work is needed to separate the impact of the two habit manifestations more rigorously. Nonetheless, findings qualify calls for habit-based interventions by suggesting that behaviour maintenance may be better served by habitual instigation and that disrupting habitual behaviour may depend on overriding habits of instigation. Greater precision of measurement may help to minimize confusion between habitual instigation and execution.